Conserving the Heritage District of Malolos: Birthplace of the First Philippine Republic Amidst the Threat of Commercialization - Estacio, Dennis L. (Recent Trends in Arts and Social Studies Vol. 3, 2023)
This chapter discuss regarding conservation of the historical town of Malolos, its rich cultural heritage through conservation management. Cultural heritage refers to all the components that were essential for human society to function. These, both tangible and intangible, are passed through generations undergoing changes with time. This study will pursue by providing a conservation management plan to rescu e Kamestizuhan, the Heritage District of Malolos, to withstand the effects of commercialization to urban morphology. This chapter presents the research methods and techniques, the sample of the study, the research instruments, the data collection, and the data processing and statistical treatment used. The historical context was established through a review of archival materials. Relevant documents from the Malolos City Government were gathered and reviewed to determine the past and present plan of action, if there is one, in protecting and preserving the heritage district. To ascertain the effects of commercialization in Kamestizuhan Heritage District, records of Malolos' socioeconomic profile were also examined. There is no regulation or clear policies being strictly implemented by the local government to safeguard and protect the Heritage District of Malolos Zones, according to interviews with politicians, local historians, academics, conservationists, and other stakeholders. The result of comparative analysis shows that since 2001 that Malolos became a heritage zone, it has produced three Ordinances, with No IRR unlike Vigan and Iloilo. The absence of IRR was affirmed by the documentary evidence, testimonials of the interviewees, and supported by the result of the conducted survey. With the use of the comparative historical method, local historic towns with successful conservation approach were compared to serve as guide in determining applicable considerations for the proposal. Photo-documentation, the use of mapping and inventory led to the discovery that some ancestral homes had been destroyed and sold as a result of commercialization. Survey results also indicate that the majority of the population is not very knowledgeable about Kamestizuhan's historical significance. In the end, the study developed guidelines for protecting Malolos' Kamestizuhan Heritage District from commercialization.